PENGARUH SIKAP DEMOKRATIS TERHADAP PRESTASI BELAJAR SISWA SMA NEGERI 2 BENGKALIS - Deya Rhama Dhanty; Ahmad Eddison; Supentri Supentri (KOLONI, 2022)
This research is motivated by the importance of inculcating a democratic attitude for students. The young generation who are faced with the era of globalization, where technology is developing rapidly creates a sense of individualism and self-centeredness. A democratic attitude contains positive attitudes in life so it is important to apply it because it forms identity, controls selfishness, individuality, and mutual respect between students. The implementation of these attitudes is expected to have an effect on the learning achievement obtained by the students of SMA Negeri 2 Bengkalis. This type of research is quantitative research using statistical analysis techniques. The data collection instrument used is a questionnaire. The population in the study consisted of 651 students and the sample taken was 10% of the total population, namely 66 students. Based on the results of the study, it can be seen that the democratic attitude towards student achievement in SMA Negeri 2 Bengkalis is at a moderate level. The results of the processing of the research data obtained that Fcount is 15,747 and Ftable is 3,99, where Fcount > Ftable so that it can be concluded that Ho is rejected and Ha is accepted. The magnitude of the influence of democratic attitudes on student achievement in SMA Negeri 2 Bengkalis is categorized as moderate according to the results of data processing where the value of the relationship (R) is 0.444. The result of the processed data is the coefficient of determination (R Square) of 0.197 which implies that the influence of the independent variable, namely democratic attitudes towards the dependent variable, is 19.7% of learning achievement, while the other 80.3% are factors not examined in this study. Keywords : Influence, Attitude, Democratic, Learning Achivement